Effect of medical nutrition therapy on vitamin C and malondialdehyde in HIV positive malnourished children - Dias, Bina F.; Nimkar, Aparna Dilip (International Journal of Research in Medical Sciences, 2017)
Background: The objective is to assess the effect of medical nutrition therapy on biochemical parameters like Vitamin C and Malondialdehyde by estimating oxidative stress in HIV positive malnourished childrens’ sample. Any alteration in the antioxidant markers can help to assess the effectiveness of MNT as a therapeutic agent. There is limited data on the use of Ready to Use Therapeutic Food (RUTF) in India. Therefore, the study was conducted to determine the effect of prepared Ready to Use Therapeutic Food (RUTF) also termed as Medical Nutrition Therapy (MNT) in HIV positive malnourished children. Methods: In this prospective comparative study, pre MNT and post MNT sample as well as the parameters-Malondialdehyde and Vitamin C were analyzed in 19 HIV positive malnourished children in the age group of 6-12 years at L.T.M.M. College. HIV positive malnourished children showed adverse effects on nutrition as well as immune system. Thus, to supply adequate micronutrients and macronutrients, the subjects were treated with Medical Nutrition Therapy (MNT). Results: The post MNT HIV positive malnourished childrens’ samples revealed significant results than pre MNT HIV positive malnourished childrens’ samples. Conclusions: The level of antioxidant marker (vitamin C) increased and peroxidation marker (MDA) decreased post medical nutrition therapy. The increased post levels of vitamin C activity helped in the eradication of excess free radicals, thereby reducing oxidative stress and hence the oxidative damage to cells as well as inhibiting lipid peroxidation (which is indicated by decreased post level MDA).